Short-term effect of supplemental yeast extract without or with feed enzymes on growth performance, immune status and gut structure of weaned pigs challenged with Escherichia coli lipopolysaccharide. Issue 1 (December 2016) - Waititu, Samuel; Yin, Fugui; Patterson, Rob; Rodriguez-Lecompte, Juan; Nyachoti, Charles
Abstract Background This study investigated the response of piglets receiving a yeast extract without or with a multi-enzyme mixture compared with an antimicrobial growth promoter (AGP) on performance, immune status and gut structure after anE. coli lipopolysaccharide (LPS) challenge. Thirty-six pigs were allotted to six treatments including: a non-challenged control (NCC); LPS-challenged control (CC); CC + AGP; CC + yeast extract; CC + enzymes; and CC + enzymes + yeast extract. On d 7, pigs were bled and thereafter injected with LPS or sterile saline. Blood samples were collected at 6, 48, and 96 h post-challenge. After 96 h post-challenge, pigs were euthanized to obtain duodenal, jejunal and ileal samples. Results Overall (d 1 to 11), compared with CC pigs, AGP attenuated the LPS-induced reduction in ADG (P  = 0.004), ADFI (P  = 0.03) and gain/feed ratio (P  = 0.01). At 6 h post-challenge, AGP pigs had lower plasma urea N (PUN;P  = 0.02) and serum TNF- α concentration (P  = 0.07), and higher platelet count (P  = 0.04) and serum IL-10 concentration (P  = 0.02) than CC pigs. At 48 h post-challenge, AGP pigs had lower PUN (P  = 0.02) than CC pigs, whereas enzymes + yeast extract interacted non-additively (P  = 0.001) to reduce PUN. At 96 h post-challenge, AGP pigs had lower PUN (P  = 0.02) and higher duodenal (P  = 0.03), jejunal (P  = 0.01) and ileal (P  = 0.07) villus height than CC pigs. In addition, enzymes + yeast extract interacted additively and non-additively to reduce ileal IFN-γ (P  < 0.0001) and IL-10 (P  = 0.012) expression, respectively. Generally, no differences (P  > 0.10) were observed between AGP and enzymes + yeast extract pigs on other measured parameters except for the downregulation of ileal IFN-γ (P  < 0.0001) and TNF-α (P  = 0.003) in enzymes + yeast extract pigs at 96 h post-challenge. Conclusions The LPS challenged piglets receiving enzymes + yeast extract showed beneficial responses in gut structure and immunity commensurate with those receiving antibiotics, though the latter had better overall growth performance.